2020
DOI: 10.3389/fphys.2020.593026
|View full text |Cite
|
Sign up to set email alerts
|

Blood–Brain Barrier Leakage Is Increased in Parkinson’s Disease

Abstract: BackgroundBlood–brain barrier (BBB) disruption has been noted in animal models of Parkinson’s disease (PD) and forms the basis of the vascular hypothesis of neurodegeneration, yet clinical studies are lacking.ObjectiveTo determine alterations in BBB integrity in PD, with comparison to cerebrovascular disease.MethodsDynamic contrast enhanced magnetic resonance images were collected from 49 PD patients, 15 control subjects with cerebrovascular disease [control positive (CP)] and 31 healthy control subjects [cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
115
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 71 publications
(94 reference statements)
1
115
0
Order By: Relevance
“…Thus, the immune system has evolved to deal effectively with infection, however various genetic and other factors can conspire to result in inappropriate or chronic inflammation in response to altered proteins or self-antigens that manifests in autoimmune and inflammatory disease (131). Neuroinflammation associated with disorders such as Alzheimer's disease and PD attracts peripheral immune cells to the CNS, and the disruption of the BBB which is a pathological feature of these diseases means that there is a pathway for these cells to enter the brain parenchyma (132)(133)(134).…”
Section: An Emerging Role For the Peripheral Immune System In Parkinson's Diseasementioning
confidence: 99%
“…Thus, the immune system has evolved to deal effectively with infection, however various genetic and other factors can conspire to result in inappropriate or chronic inflammation in response to altered proteins or self-antigens that manifests in autoimmune and inflammatory disease (131). Neuroinflammation associated with disorders such as Alzheimer's disease and PD attracts peripheral immune cells to the CNS, and the disruption of the BBB which is a pathological feature of these diseases means that there is a pathway for these cells to enter the brain parenchyma (132)(133)(134).…”
Section: An Emerging Role For the Peripheral Immune System In Parkinson's Diseasementioning
confidence: 99%
“…In addition, BBB leakage of fibrin and hemosiderin was observed in the striatum of PD patients ( Gray and Woulfe, 2015 ). Subtle BBB disruption in PD patients is observed in the substantia nigra, white matter and posterior cortical regions ( Al-Bachari et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that SARS-COV-2 infection can either exacerbate pre-existing neurological disorders or complicate COVID-19 disease (20,21). Pre-existing neurological disorders, such as dementia, Parkinson disease, and stroke, are associated with a disrupted blood-brain barrier and vulnerability to infection and inflammatory states (22)(23)(24). SARS-COV-2 infection might reach the brain through olfactory nerves and other neurotropic or hematogenous routes (25).…”
Section: Discussionmentioning
confidence: 99%